Three-dimensional reconstruction of a nickel- alumina composite coating by FIB-SIMS - Chater, Richard J.; Corni, Ilaria; Boccaccini, Aldo R.; Ryan, Mary P. (Surface and Interface Analysis, 2011)
The alumina particle distribution in a nickel-alumina composite coating on stainless steel was determined using the aluminum secondary ion images that were generated by sputtering a cross-section of the coating with a highly focused gallium primary ion beam (FIB). Thin slices of the coating were removed using the same beam with further imaging of the fresh surface which was very smooth despite the difference in the sputter rates of the two materials. Sequential SIMS imaging and sectioning resulted in a sequence of images from which the 3D distribution of the alumina particles in the composite coating was reconstructed. Copyright © 2010 John Wiley & Sons, Ltd.
UnivIS-Import:2015-03-09:Pub.2011.tech.IW.LM.threed
Keywords: 3D reconstruction; alumina particle; FIB-SIMS; nickel coating; SIMS imaging